The effects of perceived service fairness on satisfaction among customers in TM Point Taiping Perak / Mohamad Amirul Zharif Mohd Azlee - Mohd Azlee, Mohamad Amirul Zharif (Faculty of Business and Management, 2014)
Purpose-Customer satisfaction in a telecommunication company such as TM Point is very much anticipated in terms of fairness either by the higher-ups of TM itself, the customers or the researchers. Therefore, the purpose of this study is to create a clearer picture on how effective service fairness can be when it comes to affecting the customer satisfaction itself. Problem Statement-Decreasing monthly sales in TM as well as numerous complaints received by TM Point might be a sign that customers are not satisfied and it could also be a sign that customers feel that they are unfairly treated by the staffs in a service operation. Objective-To find the relationship between all the elements of perceived service fairness (IV) and customer satisfaction (DV) in TM Point and also to find the rank of all the elements as well as finding the most influencing factor that affects customer satisfaction together with the provision of recommendations to improve customer satisfaction in TM Point. Methodology-A close-ended questionnaire survey is conducted with a sample size of 100 respondents within Taiping town region. SPSS version 20.0 is used to find the data reliability, frequencies of data, correlation test and regression test in order to test all the hypothesis involved and to also answer all the objectives that present. Summary of The Findings-The result shows that all items of perceived service fairness are positively associated with customer satisfaction. The result shows that the highest rank of all elements is perceived distributive fairness and it is also the most influencing factor that affects customer satisfaction.